Logistic Regression Analysis for Uncovering Socio-demographic Factors of Community Participation in Waste Management - Kholil Majid; Meidiana, Christia; Adrianto, Dimas Wisnu; Ghosh, Ratan Kumar (Jurnal Pembangunan dan Alam Lestari, 2024)
This study presents the results of a preliminary attempt to assess community acceptance in an Indonesian village where a community-based waste management program is economically more attractive than simply burning or burying the waste. In Karangan Village, Bojonegoro, domestic waste is mostly burnt or buried, contributing to environmental degradation, such as water, soil, and air pollution caused by smoke. Regression analysis was applied to calculate and analyze the data. Photo mapping on current waste management (WM) practices was provided beforehand to identify its effect on the environment. The study indicates that there were about 18 illegal dumping sites in the village, which are frequently open-burnt by villagers, emitting odor and smoke, deteriorating the air quality. Low community participation in rural waste management, only 56.6%, causes improper WM. The study emphasizes the significant role of individual characteristics, age, education, motivation, opinion, willingness to be involved, sense of responsibility, information about 3R and 3R counseling, availability on dissemination, and training on waste management in influencing individuals' participation in community activities. Keywords: rural waste management, waste reduction